Parental occupational pesticide exposure and the risk of childhood leukemia in the offspring: Findings from the childhood leukemia international consortium. Issue 9 (4th April 2014) - Bailey, Helen D.; Fritschi, Lin; Infante‐Rivard, Claire; Glass, Deborah C.; Miligi, Lucia; Dockerty, John D.; Lightfoot, Tracy; Clavel, Jacqueline; Roman, Eve; Spector, Logan G.; Kaatsch, Peter; Metayer, Catherine; et al.
<x xml:space="preserve">Abstract</x> Maternal occupational pesticide exposure during pregnancy and/or paternal occupational pesticide exposure around conception have been suggested to increase risk of leukemia in the offspring. With a view to providing insight in this area we pooled individual level data from 13 case‐control studies participating in the Childhood Leukemia International Consortium (CLIC). Occupational data were harmonized to a compatible format. Pooled individual analyses were undertaken using unconditional logistic regression. Using exposure data from mothers of 8, 236 cases, and 14, 850 controls, and from fathers of 8, 169 cases and 14, 201 controls the odds ratio (OR) for maternal exposure during pregnancy and the risk of acute lymphoblastic leukemia (ALL) was 1.01 [95% confidence interval (CI) 0.78, 1.30] and for paternal exposure around conception 1.20 (95% 1.06, 1.38). For acute myeloid leukemia (AML), the OR for maternal exposure during pregnancy was 1.94 (CI 1.19, 3.18) and for paternal exposure around conception 0.91 (CI 0.66, 1.24.) based on data from 1, 329 case and 12, 141 control mothers, and 1, 231 case and 11, 383 control fathers. Our finding of a significantly increased risk of AML in the offspring with maternal exposure to pesticides during pregnancy is consistent with previous reports. We also found a slight increase in risk of ALL with paternal exposure around conception which appeared to be more evident in children diagnosed at the age of 5 years or more and those with T cell ALL which raises interesting questions on possible mechanisms.